The association of HTR3A mRNA expression and craving in Han Chinese alcohol-dependent patients: a preliminary study. (3rd May 2016) - Xu, Ya-Hui; Wang, Lin-Lin; Shi, Le; Lei, Jin-Ping; Miao, Qin; Liu, Tie-Qiao; Hao, Wei; Lu, Lin; Zhang, Rui-Ling
ABSTRACT: Background : 5-Hydroxytryptamine (5-HT) 3 receptor plays a crucial role in craving of alcohol dependence. Recent evidence shows that chronic alcohol exposure causes changes in gene expression and induces behavioral changes. However, the relationship between gene expression of 5-HT3 receptor and craving in alcohol-dependent patients is not fully understood. Objectives : The aim of this preliminary study was to investigate the relationship between gene expression of the 5-HT3 receptor and craving in alcohol-dependent patients and the epigenetic mechanism. Methods : We recruited 50 male Han Chinese alcohol-dependent patients and 46 male Han Chinese healthy controls. We investigated the changes of HTR3A mRNA, which encodes the 5-HT3 receptor A subunit, and H3K9 acetylation in HTR3A promoter region. Obsessive Compulsive Drinking Scale (OCDS) was used to assess the craving of alcohol-dependent patients relative to controls. Results : HTR3A mRNA expression levels and acetylation levels of H3K9 in the HTR3A promoter region were significantly higher in the alcohol-dependent patients. HTR3A mRNA expression levels were positively correlated with OCDS scores. Moreover, HTR3A mRNA expression levels were positively correlated with acetylation levels of H3K9 in HTR3A promoter region. Conclusion : The current findings suggest that HTR3A mRNA expression levels were positively correlated with craving in Han Chinese alcohol-dependent patients. The regulation of H3K9 histone acetylation in HTR3A promoter region may offer a target for the treatment of alcohol dependence.